Factors determining internal auditors’ behavioral intention to use computer-assisted auditing techniques: an extension of the UTAUT model and an empirical study - Ahmad Almagrashi; Abdulwahab Mujalli; Tehmina Khan; Osama Attia (Future Business Journal)
Abstract Purpose Computer-assisted audit techniques (CAATs) are used by auditors to automate some of their tasks. Since most transactions in accounting are computerized, auditing of accounting data follows this process as well. During the last two decades, many studies on technology acceptance have been published, and several new models proposed. This study aims to develop and empirically test a model to predict the factors affecting internal auditors’ behavioral intentions regarding CAATs. Design/methodology/approach This study explored the behavioral intention to use CAATs from the perspective of internal auditors by applying the extended unified theory of acceptance and use of technology (UTAUT) model. Added to this were satisfaction, trust, and organizational influence to understand people’s usage traits. Through an online survey the data were gathered from internal auditors in all Saudi public sector agencies. Structural equation modeling helped to analyze the data and support hypotheses or otherwise. Findings Effort expectancy, performance expectancy, social and organizational influences, facilitating conditions, trust, satisfaction, and behavioral intention are the main drivers of CAATs. Practical implications This study contributes to existing technology theory by expanding our understanding of the factors influencing CAATs adoption. Moreover, comprehending those determinants is extremely important to legislators. regulators and policymakers in the public sector. This study increases our knowledge about the adoption of CAATs by addressing it at the individual level instead of the organizational level. The results are consistent with the UTAUT model and deliver a practical reference for public sector officials and decision-makers involved in designing CAATs for government departments.